An assessment of the share contributions of distortion sources for various load parameters - Aleksandr Skamyin; Yaroslav Shklyarskiy; Iuliia Dobush; Vasiliy Dobush; Tole Sutikno; Mohd Hatta Jopri (Institute of Advanced Engineering and Science, 2022)
The method for assessing the contributions of distortion sources based on measuring consumer currents and calculating their projections onto the supply current vector is considered in the paper. Determination of contributions is carried out on the basis of the developed model of an industrial enterprise in the food industry in MATLAB Simulink software. This study presents various cases of simulation, including variable parameters of linear and non-linear consumer load, changes in parameters of external distortion sources and passive harmonic filters. It is shown that the considered method gives correct results in the absence of external distortions in the electrical grid. The considered criteria for the share contributions make it possible to estimate the most efficient place for installing a passive filter in the absence of external distortions. An indicator for evaluating external distortions has also been developed based on calculating the projection of the harmonic system current onto the harmonic current of the shunt filter at the considered frequency.